Some special aspects in the obligations of the parties to the lease agreement - Igor V. Mashtakov (Jus Strictum)
Today, the general and special provisions of the Civil Code of the Russian Federation on the lease agreement provide a possibility to distinguish some special aspects in the obligations of the parties, which may indicate certain problems when complying with such obligations. Therefore, the author tried to identify the problems associated with this and subjected the main obligations of the parties to the lease agreement to a certain analysis. As a result, the issues associated with the achievement of the main user effect by the parties to the lease agreement, allowing the lessor and the lessee to be satisfied with the concluded agreement, came into focus of the author. Mainly by means of the formal-legal method of research, methods of system and comparative analysis, the author discovered some problems associated with the obligations of the lessor to create and ensure conditions for the proper possession and use of the leased property, as well as the obligations of the lessee for conforming use of such property, its proper maintenance and necessary service. The obtained results of the study allow the author to say that the norms of civil legislation on lease can be specified in the sphere of the lessee’s implementation of his obligation for proper use of the leased property, taking into account the counter specification of the lessor’s obligation to create and provide appropriate conditions for this. The author came to the general conclusion that the proposed specification of the provisions of civil legislation cannot be completely replaced at the discretion of the parties in the lease agreement. The main result of the study is that the problem of improper use or actual non-use of property during the term of the lease agreement creates certain difficulties for the lessor, which could be avoided by more detailed legal regulation of the relevant obligations of the lessee, as well as some general obligations of the parties to the agreement.